2016
DOI: 10.1016/j.nbd.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal inflammation leads to impaired glutamate homeostasis and up-regulation of glutamate carboxypeptidase II in activated microglia in the fetal/newborn rabbit brain

Abstract: Astrocyte dysfunction and excessive activation of glutamatergic systems has been implicated in a number of neurologic disorders, including periventricular leukomalacia (PVL) and cerebral palsy (CP). However, the role of chorioamnionitis on glutamate homeostasis in the fetal and neonatal brains is not clearly understood. We have previously shown that intrauterine endotoxin administration results in intense microglial ‘activation’ and increased pro-inflammatory cytokines in the periventricular region (PVR) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 125 publications
(150 reference statements)
2
70
1
Order By: Relevance
“…146 Conversely, maternal inflammation has been shown to increase microglial GCPII expression in neonate brain, which would reduce endogenous mGluR3 stimulation by NAAG. 187 Taken together, these studies suggest that various DNC mechanisms that normally serve to inhibit feedforward cAMP–calcium signaling in dlPFC layer III microcircuits may be reduced in schizophrenia subjects.…”
Section: Relevance Of Dynamic Network Connectivity To Schizophreniamentioning
confidence: 86%
“…146 Conversely, maternal inflammation has been shown to increase microglial GCPII expression in neonate brain, which would reduce endogenous mGluR3 stimulation by NAAG. 187 Taken together, these studies suggest that various DNC mechanisms that normally serve to inhibit feedforward cAMP–calcium signaling in dlPFC layer III microcircuits may be reduced in schizophrenia subjects.…”
Section: Relevance Of Dynamic Network Connectivity To Schizophreniamentioning
confidence: 86%
“…With regard to site of action, although the increased expression in IBD patients has been reported in epithelial cells (6) it is also possible that inhibition of FOLH1/ GCPII may affect the enteric nervous system or infiltrating immune cells. Of interest, our laboratory recently found that GCPII is highly upregulated in microglial cells (e.g., the immune cells of the brain) following inflammation and its inhibition prevents neurological damage (27). With respect to enzymatic mechanism, to date there are 3 known FOLH1 /GCPII substrates that could be implicated as possible mediators of the therapeutic effect, including N-acetylaspartylglutamate (NAAG) (28), folate polyglutamate (2931), and laminin-derived peptides (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental procedures were approved by the Johns Hopkins University Animal Care and Use Committee (IACUC). After one week of acclimation, the pregnant rabbits underwent laparotomy on gestational day 28 (G28) and received a total of 4,800 EU of LPS ( E. coli serotype O127:B8, Sigma‐Aldrich, St. Louis, MO) injection along the wall of the uterus as previously described . The kits were induced on G30 with intravenous injection of Pitocin (0.2 unit/kg) and kept in incubators with the temperature of ∼32–35°C and relative humidity of ∼50–60%.…”
Section: Methodsmentioning
confidence: 99%